Corn pith weevil, Geraeus penicillus (Coleoptera: Curculionidae), in transgenic, insect‐resistant and conventional field corn hybrids. (22nd March 2013) - Bohnenblust, E.; Breining, J.; Roth, G.; Tooker, J.
Abstract: The corn pith weevil Geraeus penicillus (Herbst) is occasionally found boring in corn stalks throughout the eastern and Midwestern United States. Injury caused by G. penicillus is not typically economical, but may be confused with that of the European corn borer Ostrinia nubilalis (Hubner), an important economic pest throughout the United States. During efforts to assess European corn borer infestations, we discovered G. penicillus in field corn in south‐eastern Pennsylvania, including hybrids genetically modified (i.e. Bt hybrids) to control European corn borer among other herbivore species. Our analysis across sites indicated that tunnels of G. penicillus were significantly more abundant in transgenic Bt hybrids than non‐Bt hybrids, but comparisons of Bt hybrids and their near isolines revealed mostly similar numbers of G. penicillus tunnels, suggesting other hybrid features might be affecting the distribution of G. penicillus . Tunnels of G. penicillus were equally distributed among the three transgenic trait packages represented in our study. In plants where we found G. penicillus, tunnels were more abundant in stalks free of European corn borer damage. Our report appears to be the first to note G. penicillus feeding in Bt corn hybrids. These findings are notable because they document insect damage in Bt hybrids that may be mistaken for European corn borer damage and may provide evidence of an insect herbivore proliferating following a mild winter or possibly even moving into competitor‐free space.